The IL-8 protease SpyCEP is detrimental for Group A Streptococcus host-cells interaction and biofilm formation - Andreoni, Federica; Ogawa, Taiji; Ogawa, Mariko; Madon, Jerzy; Uchiyama, Satoshi; Schuepbach, Reto A.; Zinkernagel, Annelies S. (Frontiers in Microbiology, 2014)
SpyCEP-mediated chemokine degradation translates into more efficient spreading and increased severity of invasive Group A Streptococcus (GAS) infections, due to impaired neutrophil recruitment to the site of infection. SpyCEP is markedly up-regulated in invasive as compared to colonizing GAS isolates raising the question whether SpyCEP expression hinders bacterial attachment and thus colonization of the host. To address this question we used a molecular approach involving the use of homologous GAS strains either expressing or not SpyCEP or expressing an enzymatically inactive variant of SpyCEP. We found that expression of enzymatically functional SpyCEP lowered GAS adherence and invasion potential towards various epithelial and endothelial cells. SpyCEP also blunted biofilm formation capacity. Our data indicate that expression of SpyCEP decreases colonization and thus might be detrimental for the spreading of GAS.